Incorporating Psychological Approach in Nurturing the Inmates: Solution for Better Correctional System - Rina Rohayu H; Absori Absori; Natangsa Surbakti (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
Correctional facility has duty and strategic function in implementing the imprisonment and nurturing the inmates. The existing regulations are unble to solve the problems within the correctional system. The purpose of this study is to find out better solution with regard to the nurturing process of the inmates. This study employs doctrinal or normative approach. It is found that many inmates involve in criminal activities during the nurturing process. Furthermore, the inmates often become recidivists either by repeating the previous crime or conducting the new one. These facts show that the application of the existing regulations fail to change the inmates’ behavior. Self-conscience of the inmates is a determinant factor and therefore, psychological approach needs to be incorporated in the nurturing process. This can be done especially by providing psychotherapy for the inmates